FAM92A Underlies Nonsyndromic Postaxial Polydactyly in Humans and an Abnormal Limb and Digit Skeletal Phenotype in Mice. - Schrauwen, Isabelle; Giese, Arnaud Pj; Aziz, Abdul; Lafont, David Tino; Chakchouk, Imen; Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Acharya, Anushree; Khan, Falak Sher; Ullah, Asmat; Nickerson, Deborah A; Bamshad, Michael J; et al. (J Bone Miner Res, 2019)
Polydactyly is a common congenital anomaly of the hand and foot. Postaxial polydactyly (PAP) is characterized by one or more posterior or postaxial digits. In a Pakistani family with autosomal recessive nonsyndromic postaxial polydactyly type A (PAPA), we performed genomewide genotyping, linkage analysis, and exome and Sanger sequencing. Exome sequencing revealed a homozygous nonsense variant (c.478C>T, p.[Arg160*]) in the FAM92A gene within the mapped region on 8q21.13-q24.12 that segregated with the PAPA phenotype. We found that FAM92A is expressed in the developing mouse limb and E11.5 limb bud including the progress zone and the apical ectodermal ridge, where it strongly localizes at the cilia level, suggesting an important role in limb patterning. The identified variant leads to a loss of the FAM92A/Chibby1 complex that is crucial for ciliogenesis and impairs the recruitment and the colocalization of FAM92A with Chibby1 at the base of the cilia. In addition, we show that Fam92a homozygous mice also exhibit an abnormal digit morphology, including metatarsal osteomas and polysyndactyly, in addition to distinct abnormalities on the deltoid tuberosity of their humeri. In conclusion, we present a new nonsyndromic PAPA ciliopathy due to a loss-of-function variant in FAM92A. © 2018 American Society for Bone and Mineral Research.

A novel homozygous variant in BMPR1B underlies acromesomelic dysplasia Hunter-Thompson type. - Ullah, Asmat; Umair, Muhammad; Muhammad, Dost; Bilal, Muhammad; Lee, Kwanghyuk; Leal, Suzanne M; Ahmad, Wasim (Ann Hum Genet, 2018)
Acromesomelic dysplasia is genetically heterogeneous group of skeletal disorders characterized by short stature and acromelia and mesomelia of limbs. Acromesomelic dysplasia segregates in an autosomal recessive pattern and is caused by biallelic sequence variants in three genes (NPR2, GDF5, and BMPR1B). A consanguineous family of Pakistani origin segregating a subtype of acromesomelic dysplasia called Hunter-Thompson was clinically and genetically evaluated. Genotyping of microsatellite markers and linkage analysis revealed a 7.78 Mb homozygous region on chromosome 4q22.3, which harbors BMPR1B. Sequence analysis of the gene revealed a novel homozygous missense variant (c.1190T > G, p.Met397Arg) that segregates with the disease phenotype within the family and produced a Logarithm of odds (LOD) score of 3.9 with the disease phenotype. This study reports on the first familial case of acromesomelic dysplasia Hunter-Thompson type. It is also the first report of BMPR1B underlying the etiology of acromesomelic dysplasia Hunter-Thompson type.

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing